Design and control of electric vehicle charger - Zakaria, Zulailah (2015)
Nowadays, the demand for electric vehicle (EV) production increases because this type of transportation provides an alternative to the conventional vehicle that uses power by fossil fuels and reducing the dependence on use of gasoline. Moreover, EV also is introduced in car sharing and mobility concept to overcome traffic congestion problem in the urban area. In order to familiarize with the process of the EV charger, an on-board EV charger is designed with introduction of some controllers for controlling charging process. The topology consist of two stages of conversion, which the first part for AC/DC conversion and power factor correction (PFC) while the second part for DC/DC conversion and galvanic isolation. In order to control the first part, a small signal model for PFC boost is introduced to control the output voltage and input current. This PFC boost controller is designed using PI control and designed to control two loops. The loops are voltage control loop (known as outer loop) and current control loop (known as inner loop). For the second stage, the constant current charging method is introduced to control the charging process of an on-board EV charger within its specification limit. The simulation is done with the help of MATLAB software and the result from Simulink will demonstrate the effectiveness of the design and its implementation. Furthermore, the proposed design of the EV charger reduces the percentage of THD and produce unity power factor that contributes in the stability for the EV charger.